Hyperhomocisteinemia, hypercysteinemia, glutamate excitotoxicity, taurine deficiency at hepatitis C - V. K. Pozdeev; N. V. Pozdeev; O. Ye. Nikitina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. An estimation of metabolic disorders related to chronic course of hepatitis C.Material and methods. Total homocysteine (tHCy), total cysteine (tCys), total glutathione (tGSH) and free aminoacids (Asp, Asn, Glu, Gln, Tau, Ser) levels were measured by high-performance liquid chromatography in plasma of 55 hepatitis C patients and 14 healthy volunteers.Results. Total statistical data processing at hepatitis C revealed: hyperhomocisteinemia (2,5 times increase in tHCy level), hypercysteinemia (1,5 times increase in tCys level), glutamate excitotoxicity (2,75 times increase in Glu level on a background of relative decrease of levels of tGSH and Gln), deficiency of taurine (level was decreased 1,4 times), increase of Gln, Asp, Asn, Ser levels 1,56, 1,75, 1,32, 1,4 times respectively. Data processing by nonnormal histogram plotting of substances plasma levels in hepatitis C patients revealed heterogeneity of pathochemistry of hepatitis C for tGSH, tCys and Gln. However in sets both with relatively low and high levels of these substances content of tHCy, Glu and Asp remains increased and reflects hyperhomocisteinemia and glutamate excitotoxicity phenomena. In patients with high content of tGSH and Gln in blood glutamate excitotoxicity was less expressed — levels of tHCy, Glu and Asp were increased to lesser degree, strong positive correlation between tGSH, Gln, tCys and Ser was marked.Conclusion. Metabolic therapy can essentially decrease negative effect of metabolic disorders and increase efficacy of PEG-IFN-α in combination to ribavirin at hepatitis C treatment.